Forecasting the Number of Child Development Therapy Patients at Mentari Anakku Clinic Tangerang in 2021 with the Double Exponential Smoothing Method - Nurbaiti, Haliza; Siregar, Rosman (Talenta Publisher, 2022)
Clinic is a health service facility that organizes and provides basic and specialist medical services, organized by more than one type of health worker and led by a medical worker. This study aims to determine fluctuations and predict the number of therapy patients at the Child Development Clinic (Mentari Anakku) using the time series method, namely double exponential smoothing. Based on the results of the forecast using the double exponential smoothing method in the 2021 period, it is known that the total number of child development therapy patients is 7,062 people. It can be seen that the total number of patients has increased quite significantly and it is necessary for the clinic to improve the performance of the workers.